Detection of Toxoplasmosis in Cows Slaughtered at the Oeba Slaughterhouse, Kupang - Diana Agustiani Wuri; Julianty Almet; Maria Serlianty Apong (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2020)
Toxoplasmosis, caused by Toxoplasma gondii, is one of the most common parasitic infections of humans and other warm-blooded animals in most parts of the world. The present study aimed to determine the presence of T. gondii in cattle slaughtered in Oeba Kupang Abatoir, and to identify associated risk factors through a qualitative descriptive method through literature study approach. Sera were collected from 15 cattle and tested for antibodies against T.Gondii using Anigen Rapid Toxoplasma Ab Test Kit. The results showed that there were 2 positive samples infected with Toxoplasma (13.33%). The presence of cats and the number of cats in the farms stood out as an important risk factor.